rPrism: a software for reactive weighted state transition models - Figueiredo, Daniel (2019)
In this work we introduce the software rPrism, as a branch of the software PRISM model checker, in order to be able to study weighted reactive state transition models. This kind of model gathers together the concepts of reactivity { which consists of the capacity of a state transition model to alter its accessibility relation { and weights, which can be seen as costs, rates, etc.. Given a speci c model, the tool performs a simulation based on a Continuous Time Markov Chain. In particular, we show an example of its application for biological systems.